2002
DOI: 10.1101/gad.1025602
|View full text |Cite
|
Sign up to set email alerts
|

Nob1p is required for biogenesis of the 26S proteasome and degraded upon its maturation in Saccharomyces cerevisiae

Abstract: Nob1p is a nuclear protein that forms a complex with the 19S regulatory particle of the 26S proteasome and with uncharacterized nuclear protein Pno1p. Overexpression of NOB1 overrode the defects in maturation of the 20S proteasome of ump1⌬ cells, and temperature-sensitive nob1 and pno1 mutants exhibited defects in the processing of the ␤ subunits and in the assembly of the 20S and the 26S proteasomes. A defect in either NOB1 or PNO1 caused accumulation of newly formed Pre6p in the cytoplasm, whereas Pre6p of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 51 publications
7
84
0
Order By: Relevance
“…Wei-Yi Huang, Dong-Hui Chen, Li Ning, Li-Wei Wang* (NOB1p), encoded by the NOB1 gene plays a crucial role in protein degradation pathway as it binds together the 20S proteasome with the 19S regulatory particle in the nucleus to facilitate the maturation of the 20S proteasome (Tone, 2002). Recently it has been found that the down regulation of over expressed NOB1 in ovarian cancer tissues lead to the suppressed cancer cell survival.…”
Section: Sirna Mediated Silencing Of Nin1/rpn12 Binding Protein 1 Hommentioning
confidence: 99%
“…Wei-Yi Huang, Dong-Hui Chen, Li Ning, Li-Wei Wang* (NOB1p), encoded by the NOB1 gene plays a crucial role in protein degradation pathway as it binds together the 20S proteasome with the 19S regulatory particle in the nucleus to facilitate the maturation of the 20S proteasome (Tone, 2002). Recently it has been found that the down regulation of over expressed NOB1 in ovarian cancer tissues lead to the suppressed cancer cell survival.…”
Section: Sirna Mediated Silencing Of Nin1/rpn12 Binding Protein 1 Hommentioning
confidence: 99%
“…Considering the proposed role of Nob1p in proteasome maturation (Tone and Toh-e 2002), it remained formally possible that the D92N mutation affected some cellular process other than rRNA processing. To test whether the growth defects correlate with the inhibition of pre-rRNA cleavage, we performed Northern analyses of high molecular-weight RNA species from strains FIGURE 1.…”
Section: Resultsmentioning
confidence: 99%
“…The C-terminal tail of ribosomal protein rpS14 is also required for this final step in 18S rRNA maturation (Jakovljevic et al 2004). In addition, Nob1p was implicated in proteasome biogenesis (Tone and Toh-e 2002), raising the possibility that its role in 20S pre-rRNA processing might be indirect or secondary. Nob1p contains a predicted PIN domain, and the structure of an archaeal PIN domain was recently solved and shown to have structural homology to T4 phage RNase H and flap endonucleases (Arcus et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Binding of the 19S activator protein complex to either end of the 20S forms the 26S and 30S proteasomes, a process that is facilitated by the Pno1p and Nob1p chaperones (Tone and Toh-E 2002). Metabolic control of the 19S is believed to dynamically regulate the 26S proteasomes.…”
Section: Functional Proteasomes Require a Highly Regulated Assemblymentioning
confidence: 99%
“…For example, the 19S complex is formed from a base of ATPase subunits, Rpn10 and a lid of non-ATPase subunits. Combination of the 19S with the 20S proteasome is facilitated by the Pno10 and Nob1p chaperones and can interface once to form the 26S or twice to form the 30S proteasomes (Tone and Toh-E 2002). The 11S heptameric complex is composed of α, β, and γ subunits and can also interface with the 20S proteasome, forming hybrid complexes of alternative function (Kloetzel 2004).…”
Section: Figure 1 Flowchart Of Proteasome Assemblymentioning
confidence: 99%